SYSTEMATIC REVIEW PERFORMANCE EVALUATION SYSTEM IN EMERGENCY MEDICAL SERVICES (EMS) - Taslim, Risky Wulan Ramadani; Siswanto; Hayati, Yati Sri (International Journal of Psychosocial Rehabilitation, 2020)
To find out the indicators that influence the performance evaluation in Emergency Medical Services (EMS). Systematic Review through several stages of making inquiries, identification, eligibility, screening, and assessment / appraisal. Selection process contained in the framework systematically review and the results 5 articles and then each article was summarized and rated with JBI. Data from review and analysis of the five articles in this systematic review, the authors take three indicators that influence the performance evaluation in EMS that is the structure, process, and outcome. Based on a review and analysis from the authors, these indicators include performance index (such as knowledge, skill, medical protocol, out-of-hospital cardiac arrest survival, etc.), that may have different definitions in every institution or country. These indicators are metric that reflects on the performance of a system or process. As the indicator, value rises or falls, it suggests that the system or process is operating better or worse. The indicators that influence the performance evaluation in EMS are the structure, process, and outcomes.